Designing Effective Research Surveys: Methods and Challenges - Ashay Devidas Shende (AG Volumes, 2024)
This review paper delves into the complexities of survey design, a critical instrument in quantitative research. Various types of survey designs, such as cross-sectional, longitudinal, and experimental survey, are examined, each of which serves a unique research purpose. The clarification of fundamental terms in survey design is necessary to guarantee the robustness of data collection and analysis. The paper analyses a variety of survey methods, including AI surveys and interviews, and emphasises their respective benefits. Demographics is one of the challenges associated with survey research. Strategies are provided to mitigate these obstacles through the discussion of queries and leading questions. The objective of this comprehensive review is to provide researchers with the necessary information to develop surveys that are both reliable and effective.